Documenting ethnoveterinary practices of Tiruvannamalai district in Tamil Nadu, India - Vedapuri, Porchezhiyan; J. V., Ganesh; T. S., Subha; Perumal, Pandikumar; Savarimuthu, Ignacimuthu (Ethnobotany Research and Applications, 2025)
Background: Ethnoveterinary practices are prevalent in India; yet this knowledge is poorly documented. This study documents the ethnoveterinary practices in Tiruvannamalai district in Tamil Nadu, India. Methods: Using successive free listing method, 23 healers were identified and the ethnoveterinary formulations used by them were recorded. The data were analyzed using Informant Consensus Factor (Fic) and Index of Agreement Remedies (IAR). Results: A total of 120 formulations was documented for treating about 50 veterinary health conditions. Alimentary tract ailments showed high consensus followed by dermatological ailments and poisonous bites. Musculo-skeletal ailments, genito-urinary ailments, sensory organ ailments and ectoparasitic infections showed average consensus. Considerable overlap was observed between human and veterinary applications; common medicinal plants like Curcuma longa, Piper nigrum, Allium sativum, Piper betle and Azadirachta indica were regularly cited. Conclusion: This preliminary study highlights the significance of validating traditional knowledge of veterinary practices in Tamil Nadu. Key words: Animal health; Botanicals; Siddha; Traditional Indian Medicine